Pengaruh Kompetensi, Pelatihan dan Fasilitas Kerja terhadap Kinerja Pegawai dengan Komitmen Organisasional sebagai Variabel Intervening - Pujiati, Diyah; Utomo, Joko; Sumekar, Kertati (Syntax Literate, 2025)
This research aims to analyze the influence competency, training dan work facilities onemployee performance with organizational commitment as an intervening variabel (Study of property user administration officials, user property administrators and auxiliary property administrators within the Kudus Regency Government). The population in this study was 155 people. Respondents totaled 125 people. Sampling Technique: In this research, quota sampling was used. This instrument was tested using validity and reliability tests. The analysis technique used is SEM (Structural Equation Modeling) AMOS. The results of this research show, firstly, competency has a positive and significant effect on organizational commitment, secondly training has a positive and significant effect on organizational commitment, thirdly work facilities have a positive and significant effect on organizational commitment, fourth competency has a positive and significant effect on employee performance, fifthly training has a positive effect on organizational commitment. positive and significant on employee performance, the six work facilities have a positive and significant effect on employee performance, the seventh organizational commitment has a positive and significant effect on employee performance. Periodic evaluations need to be carried out through monitoring and evaluation of the OPD as a benchmark for employee performance results, so that they are able to realize the vision and mission of regional property management.